Autism's false prophets : bad science, risky medicine, and the search for a cure - Offit, Paul A. (Columbia University Press, 2010)
A London researcher was the first to assert that the combination measles-mumps-rubella vaccine known as MMR caused autism in children. Following this ""discovery, "" a handful of parents declared that a mercury-containing preservative in several vaccines was responsible for the disease. If mercury caused autism, they reasoned, eliminating it from a child's system should treat the disorder. Consequently, a number of untested alternative therapies arose, and, most tragically, in one such treatment, a doctor injected a five-year-old autistic boy with a chemical in an effort to cleanse him.